Maternal metabolic conditions as predictors of breastfeeding outcomes: Insights from an Australian cohort study - Kate Rassie; Raja Ram Dhungana; Aya Mousa; Helena Teede; Anju E. Joham (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction Breastfeeding represents an important opportunity to optimize health outcomes for both mother and infant, particularly in the context of maternal metabolic conditions such as diabetes and polycystic ovary syndrome. However, evidence suggests that women affected by these conditions breastfeed at reduced rates and durations. Our aim was to use the large, prospective, community‐based Australian Longitudinal Study on Women's Health (ALSWH) to conduct an in‐depth exploratory analysis of breastfeeding outcomes in Australian women affected by key maternal metabolic conditions. Material and Methods Data from 12 920 pregnancies to 5605 women from the 1973–1978 birth cohort of the ALSWH were examined. Univariable and multivariable regression using generalized estimating equation models were applied to assess breastfeeding initiation and duration (outcome measures) in relation to key self‐reported maternal metabolic diagnoses (pre‐gestational type 1 and type 2 diabetes, gestational diabetes, and polycystic ovary syndrome; main explanatory variables). Key sociodemographic and clinical covariates were also considered. Results Results showed no significant association between specific maternal metabolic diagnoses (pre‐gestational or gestational diabetes, or polycystic ovary syndrome) and breastfeeding outcomes. However, maternal body mass index emerged as a key predictor of suboptimal breastfeeding outcomes. Pregnancies affected by maternal obesity were associated with a 2.1‐fold increase in the odds of not initiating breastfeeding, after adjusting for other key variables (95% CI 1.67 to 2.60, p < 0.01). Maternal overweight and obesity were, respectively, associated with an adjusted 1.4‐fold (95% CI 1.20 to 1.55, p < 0.01) and 1.8‐fold increase (95% CI 1.60 to 2.10, p < 0.01) in the odds of a breastfeeding duration less than 6 months. Conclusions Maternal obesity, rather than any specific maternal metabolic condition, appears to be a key predictor of breastfeeding outcomes in Australian women.